Digital Transformation in Small Business: Understanding the Role of Trust and Social Influence in Fintech Use Intention - Siska Yulia Defitri; Nova Ramadhani; Nidia Anggreni Das; Kamisah Supian (Lembaga Publikasi Ilmiah Nusantara, 2026)
The increasing adoption of financial technology (fintech) has transformed payment practices among small and medium-sized enterprises (SMEs). However, evidence regarding the determinants of fintech usage intention among business operators in emerging regional economies remains limited. This study examines the influence of perceived ease of use, trust, and social influence on fintech usage intention among café and restaurant operators in Solok City, Indonesia. Drawing on the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT), and Trust Theory, this study employs a quantitative approach using survey data collected from 124 respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that perceived ease of use and social influence have significant positive effects on fintech usage intention, whereas trust does not. The results suggest that business owners prioritize operational convenience and social expectations over security-related considerations when adopting fintech payment systems. Furthermore, trust appears to function as a prerequisite condition rather than a direct determinant of fintech usage intention in contexts where fintech services are already widely recognized and regulated. This study contributes to the fintech adoption literature by providing evidence from SME operators in an emerging regional economy and highlighting the contextual role of trust in digital payment adoption. The findings offer practical implications for fintech providers and policymakers seeking to accelerate digital payment adoption among SMEs.